Schneider’s first-rank symptoms as predictors of remission in antipsychotic-naive first-episode psychosis - Malinowski,Fernando R. (2020)
Objective: German psychiatrist Kurt Schneider proposed the concept of first-rank symptoms (FRS) of schizophrenia in 1959. However, their relevance for diagnosis and prediction of treatment response are still unclear. Most studies have investigated FRS in chronic or medicated patients. The present study sought to evaluate whether FRS predict remission, response, or improvement in functionality in antipsychotic-naive first-episode psychosis. Methods: Follow-up study of 100 patients at first episode of psychosis (FEP), with no previous treatment, assessed at baseline and after 2 months of treatment. The participants were evaluated with the standardized Positive and Negative Syndrome Scale (PANSS) and Global Assessment of Functioning (GAF) and for presence of FRS. Results: Logistic regression analysis showed that, in this sample, up to three individual FRS predicted remission: voices arguing, voices commenting on one’s actions, and thought broadcasting. Conclusion: Specific FRS may predict remission after treatment in FEP patients. This finding could give new importance to Kurt Schneider’s classic work by contributing to future updates of diagnostic protocols and improving estimation of prognosis.